Addressing Burnout Among Generation Z Through a Bibliometric Review and the Role of Human Resource Management in Its Prevention - Rahmani, Sabrina (Westscience Press, 2025)
This study evaluates a group of 20 publications related to burnout among Generation Z. The publications were selected from various scientific journals relevant to human resource management. This study uses a descriptive bibliometric analysis method consisting of four main stages: identification, screening, eligibility, and inclusion. First, a search for scientific articles was conducted using the keywords “burnout,” “Generation Z,” and “human resource management” in databases such as Google Scholar, yielding 10,500 publications. Next, the articles were screened based on language and publication period criteria, leaving 7,650 relevant articles. Finally, after a thorough reading, 20 review articles were selected for analysis, covering the causes of burnout, its impacts, and HR management strategies for its prevention. The data was processed using VOSviewer for visualization of the interrelationships between topics.